Metadiscourse in Multimodal Discourse: The Case of About-us Pages of Chinese and American Companies - Ziling Zhu; Xinxin WU (Journal of Modern Research in English Language Studies, 2025)
A company’s about-us homepage, serving as the display page of the company’s fundamental information, constitutes an outstanding means for the company to mold and publicize its corporate image. An excellent company homepage can effectively establish a positive image of the company. Nevertheless, the English homepages of some Chinese companies do not comply with foreign expressions or images, which might impede the internationalization process of these companies. Based on a framework of metadiscourse analysis and multimodal discourse analysis, this study delved into the linguistic and cultural characteristics of the introductory discourse of Chinese and American companies. This research first labeled the types of metadiscourse, and then employed the SPSS 27.0 to analyze the data. In contrast to American companies, Chinese companies have less awareness of the utilization of verbal and visual metadiscourse, particularly interactional metadiscourse. Additionally, the employment of graphics can assist Chinese and American companies in better expressing the author’s attitude and attracting readers. This research is dedicated to integrating a metadiscourse framework and multimodal discourse analysis to analyze the metadiscourse in English introductory writing of Chinese and American companies, and provides implication for companies on how to enhance the readability of about-us page for native English speakers.